An investigation of the link between indirect tax, oil receipt, debt on foreign reserves in Nigeria - Kaka, Emmanuel John; Ado, Abdullahi Bala (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
The main objective of the study was to investigate the influence of indirect tax, direct tax, oil revenue, total debt on foreign reserves in Nigeria from 1980 to 2019. Ex post factor research design was adopted in this research and data was analyzed with the aid of Ordinary Least Square multi linear regression technique. The study found out that, there is a negative and statistically significant influence of indirect tax and direct tax on foreign reserves in Nigeria. Similarly, it was discovered that oil revenue and total debt has positive and non-statistical significant influence on foreign reserves. The study concluded that there is an influence of oil revenue and total debt on foreign reserves, as well as no influence of indirect tax and direct tax on foreign reserves. In addition, the lack of influence of indirect tax and direct tax shows that government has not being taking advantage of its taxation to generate enough revenue to meet its expenditures, as well as boost foreign reserves. And suggested that government should not depend mainly on oil revenue to meet expenditure and sustain its foreign reserves, but should try as much as possible to diversify the economy towards the creation, encouragement and sustenance of small scale and medium industries, and the development and extraction of non-oil mineral resources for export to boost its foreign reserves. Lastly, government should enhance its revenue generation in taxes to meet its expenditures to give room for the revenue generated through crude oil to increase foreign reserves.